Evaluation of the sensitivity and specificity of GST-tagged recombinant antigens 2B2t, Ag5t and DIPOL in ELISA for the diagnosis and follow up of patients with cystic echinococcosis. - Carlos Sánchez-Ovejero; Eylem Akdur; Raúl Manzano-Román; Ana Hernández-González; María González-Sánchez; David Becerro-Recio; Javier González-Miguel; Okan Akhan; Carmen M Cretu; Kamenna Vutova; Francesca Tamarozzi; Mara Mariconti; et al. (Public Library of Science (PLoS), 2020)
Cystic echinococcosis (CE) is a neglected zoonotic disease caused by Echinococcus granulosus sensu lato. Diagnosis and monitoring of CE rely primarily on imaging while serology is used as a confirmatory test. However, imaging is not always conclusive and currently available serological assays have suboptimal sensitivity and specificity, lack standardization, and are not useful for patients´ follow-up. Seroassays for CE are usually based on hydatid fluid (HF), a complex, variable antigenic mixture, and cross-reactivity exists especially with alveolar echinococcosis. Recombinant proteins based on immunogenic antigens most abundant in HF, such as AgB1, AgB2 and Ag5, have been used to overcome these limitations. None of them so far showed potential to replace HF; however, their performance have been largely tested on a limited number of samples, and comparison of different antigens using the same cohort has been rarely performed. The combination of several immunogenic epitopes in a single recombinant protein could enhance test sensitivity. For the diagnosis and follow-up of patients with CE, we compared the performance of the crude HF, previously described recombinant 2B2t antigen, and GST-tagged version of 2B2t, and novel designed recombinants (GST-Ag5t and the GST-DIPOL chimera containing AgB1, AgBB2 and Ag5 epitopes) by IgG-ELISA format. Samples belong to a retrospective cohort of 253 well-characterized patients with CE, previously described for the evaluation of the 2B2t antigen, 92 patients with alveolar echinococcosis, and 82 healthy donors. The reference standard for CE diagnosis was the presence of a CE lesion as diagnosed by ultrasonography. The highest sensitivity was obtained with HF [86.7%, 95% confidence interval (CI): 81.2-91.0], followed by GST-2B2t (70.0%, 95% CI: 63.1-76.2), 2B2t (65.5%, 95% CI: 58.5-72.0), GST-Ag5t (64.5%, 95% CI: 57.5-71.1) and GST-DIPOL (63.1%, 95% CI: 56.0-69.7). The GST-2B2t had the best specificity (95.8%, 95% CI: 88.3-99.1) and the lowest cross-reactivity (38.7%, 95% CI: 27.6-50.6). Good response to treatment also correlated to negative test results in the GST-2B2t ELISA. While none of the tested recombinant antigen appears suitable to replace HF for the diagnosis of CE, GST-2B2t should be further explored as a confirmation test, based on its high specificity and low cross-reactivity, and for the follow-up after treatment in those patients with positive serology for this antigen.